Perturbative Nonlinear Optics in the Extreme Ultraviolet Region - Dao, Lap Van; Hannaford, Peter (Communications in Physics, 2017)
We report the investigation of the wave-mixing process with two multiple-cycle pulses having incommensurate frequencies (at 1400 nm and 800 nm). With a collinear and non-collinear configuration of the two beams, a different extreme ultraviolet (XUV) mixing field can be created at low intensity of the 800 nm field. For a high intensity of the second laser pulse we are able to amplify the XUV radiation. We show that the dynamics of the free electrons can be revealed from the frequency mixing process.